Transport, ultrastructural localization, and distribution of chemical forms of lead in radish (Raphanus sativus L.) - Wang, Yan; Shen, Hong; Xu, Liang; Zhu, Xianwen; Li, Chao; Zhang, Wei; Xie, Yang; Gong, Yiqin; Liu, Liwang (Frontiers in Plant Science, 2015)
Lead (Pb), a ubiquitous but highly toxic heavy metal, is harmful to human health through various pathways including by ingestion of contaminated vegetables. Radish is a worldwide root vegetable crop with significant health and nutritional benefits. However, little is known about Pb translocation and distribution within radish plants after its uptake by the roots. In this study, Pb stress was induced using Pb(NO3)2 in hydroponic culture, aiming to characterize the transport, ultrastructural localization and distribution of chemical forms of Pb in different tissues of radish. The results showed that the majority of Pb (85.76–98.72%) was retained in underground organs including lateral roots, root heads and taproot skins, while a small proportion of Pb was absorbed by root flesh (0.44–1.56%) or transported to the shoot (1.28-14.24%). A large proportion of Pb (74.11–99.30%) was integrated with undissolved Pb oxalate, protein and pectates forming Pb-phosphate complexes. Moreover, a low-Pb-accumulating line of radish showed a higher proportion of Pb in water-soluble form compared with a high-Pb-accumulating line. Subcellular distribution analysis showed that a large proportion of Pb was bound to cell wall fraction in lateral roots (71.08–80.40%) and taproot skin (46.22–77.94%), while the leaves and roots had 28.36–39.37% and 27.35–46.51% of Pb stored in the soluble fraction, respectively. Furthermore, transmission electron microscopy (TEM) revealed Pb precipitates in intercellular space, cell wall, plasma lemma and vacuoles. Fractionation results also showed the accumulation of Pb on the cell wall, intercellular space and vacuole, and low uptake of undissolved Pb oxalate, protein, pectates and Pb–phosphate complexes, which might be due to low transport efficiency and Pb tolerance of radish. These findings would provide insight into molecular mechanism of Pb uptake and translocation in radish and facilitate development of low-Pb-content cultivars in root vegetable crops.